The Strategy of Islamic Boarding School in Promoting Moral Education Based on Local Wisdom - Nurlaela, Nurlaela; Zaki, M.; Wildan, Wildan; Mukhlis, Mukhlis; Fattah, Abdul; Hadisaputra, Prosmala (Universitas Sebelas Maret, 2024)
This current study delves into the strategies employed by Islamic boarding schools (Pesantren) in promoting character education grounded in local wisdom. The investigation is guided by a central research question: